FORMATION OF SELF-ESTEEM IN SMALL SCHOOL-AGE STUDENTS - Isaxanova Moxidil Erkinovna; Abdusattorova Farangiz Azizjon qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the level of self-esteem has a great impact on the whole life of a person, so parents should understand how important proper family upbr inging is for a child's self-esteem. that, in order to help children's self-esteem, it is necessary to support them, show them sincere care and give them positive evaluation of their actions and work as often as possible passed.